Agriculture et réforme agraire en Bolivie - Grenier, Fernand (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
One of the major impacts of the Bolivian revolution of 1952 was felt in the rural areas of this country where the campesinos still represent two thirds of the total population. In the first part of this article the various agricultural regions of Bolivia are presented with their main characteristics : the altiplano, the yungas and the lowlands of the Oriente. The effects of the agrarian reform undertaken in January 1953 are then examined. During the first years of the reform the subdivision of properties contributed to extend a subsistence economy and there were movements of résistance from the major landowners as well as from the traditional Indian communities known as the ayllus. Colonization of the fertile Oriente, mainly in the region of Santa Cruz, was an alternative which had some interesting results. Despite its limited success the experience of agrarian reform has led the Government to undertake in 1962 a new ten-year plan whose objectives are the continuation of the agrarian reform together with expansion of agricultural productions and colonization.